HUBUNGAN DIAGNOSIS KLINIS DENGAN DIAGNOSIS BIOPSI ASPIRASI JARUM HALUS PADA STRUMA DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2016 - Wien Wiratmoko (Jurnal Medika Malahayati, 2016)
To determine the relationship of clinical diagnosis and diagnosis of Fine Needle Aspiration Biopsy inStruma In Hospital Dr. H. Abdul Moeloek Lampung Province 2016.The research method used in this research is themethod of analytic research with cross sectional study. The samples used were 72 cases in dr. H Abdul MoeloekLampung Province.The results obtained with the results BAJAH ST malign as many as 18 cases (25.%) lowercompared with the results BAJAH benign as many as 15 cases (20.8%), with the result BAJAH SNT malign asmany as 6 cases (8.3%) higher than the result of benig BAJAH as 33 cases (43.8%). Based on the statisticaltest obtained by value p = 0.001 (OR = 3.545, 95% CI = 1.594 to 7.884). It can be concluded that there is a significantrelationship between the clinical diagnosis with the diagnosis BAJAH